Short Term Outcome of Drug Eluting Balloon for Percutaneous Coronary Intervention - Anwar, Maida; Nadeem, Asif; Rehman, Fahad Ur; Sarfraz, Sana; Ahmed, Iftikhar; Azad, Naseem; Siddique, Muhamad Bilal; Kamran, Javeria (Pakistan Armed Forces Medical Journal, 2023)
Objective: To assess the short-term outcome of Drug Eluting Balloon (DEB) for Percutaneous Coronary Intervention(PCI). Study Design: Analytical Cross-sectional study Place and Duration of Study: Armed Forces Institute of Cardiology/National Institute of Heart Diseases, Rawalpindi, from Jan 2022 to July 2022. Methodology: Patients who underwent DEB-PCI within the past year were chosen via Universal sampling technique. Symptomatic patients were evaluated by conventional coronary angiography, while asymptomatic patients had CTangiography. Primary outcome was restenosis rate on angiographic follow-up. Patients having